THE INFLUENCE OF IMMERSION INTO INDONESIAN BAY LEAF INFUSION TO THE QUALITY AND DURABILITY OF PORK - Agustina, Kadek Karang; Sari, Prabarini Hanum; Suada, I Ketut (Buletin Veteriner Udayana, 2017)
This research aim was to know the influence of immersion in Indonesian bay leaf ( Syzygium polyanthum ) infusion for the quality and durability of pork in room temperature (28 0 C). A total of 80 pork samples (loin) tested in the research used factorial randomized complete block design, with 2 factor such as; four factors of concentration: 0%, 5%, 10% and 15% of Indonesian bay leaf infusion, four factors of exposure time: 0, 3, 6, and 9 hours. The parameters of pork quality have checked; water holding capacity, water content, pH, color and texture. The result showed that submersion of pork in Indonesian bay leaf infusion did not affect to water holding capacity and water content of pork but showed a noticeable affect to pH, color and texture. Pork that marinated into bay leaves infusion showed a good durability during exposure in room temperature until 9 hours. It can be concluded that the infusion of bay leaves at various concentrations were able to maintain the quality of pork.
Keywords: daging babi; daun salam; kualitas; daya tahan